Challenging the Molecular Parameters of Vetiver: Can 4, 5‐Dimethyl‐3‐(3′‐methylbut‐1′‐en‐2′‐yl)‐4‐phenylcyclopent‐2‐en‐1‐one Mimic Zizaenones in Structure and Odor?. Issue 15 (2nd April 2019) - Pfaff, Patrick; Mouhib, Halima; Kraft, Philip
Abstract : In order to investigate the molecular parameters of vetiver odorants and scrutinize the significance of ziza‐6(13)‐en‐3‐ones as structural templates in the design of new vetiver odorants, 4, 5‐dimethyl‐3‐(3′‐methylbut‐1′‐en‐2′‐yl)‐4‐phenylcyclopent‐2‐en‐1‐one (10 ) was synthesized in 6 steps from cyclopentane‐1, 3‐dione (20 ) following a Stork–Danheiser strategy after synthetic approaches by Ni‐catalyzed [3+2] annulation and enyne metathesis had failed. Addition of EtOH, α‐methylation of the resulting vinylogous ester18, Pd‐catalyzed α‐arylation, and CeCl3 · 2LiCl mediated alkylation with (3‐methylbut‐1‐en‐2‐yl)lithium, generated by Shapiro reaction from the corresponding hydrazone23, furnished after a concluding α‐methylation the target compound that possessed only a weak woody odor devoid of typical vetiver characteristics. While the design approach utilizing London dispersion forces could not reveal the secret of vetiver, it showed that the molecular parameters are far more complex than initially expected. Abstract : Unfortunately Not! – While the synthesis was finally successful on a classical Stork–Danheiser route, the simplified target structure, designed to be confined by London dispersion forces to mimic zizaenones, only possesses a weak woody odor but no typical vetiver character. So, the question of the ultimate vetiver lead structure and the race for an easily accessible synthetic vetiver odorant remain open.